Efektivitas Rekrutmen dan Retensi Karyawan dalam Mengatasi Turnover Dini PT Victory International Future : Penelitian - Sahira, Alan Nadia Bella; Aminah, Siti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study analyzes the effectiveness of recruitment processes and retention strategies in addressing early employee turnover at PT Victory International Futures, Ciputra World Surabaya branch. The study used a qualitative descriptive approach with observation techniques during a four-month internship, semi-structured interviews with new employees and internal parties, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive model. The results show that high new employee turnover is influenced by recruitment that does not emphasize job fit, short initial training, an unstable performance-based compensation system, minimal adaptation assistance, and unstructured personnel administration. These findings indicate that recruitment and retention strategies are not optimal, so the study recommends strengthening selection, developing a structured onboarding program, and improving the mentoring and administration system to reduce early turnover.